2017
DOI: 10.1002/cncr.30949
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 dose escalation multicenter trial of pracinostat alone and in combination with azacitidine in patients with advanced hematologic malignancies

Abstract: Background Pracinostat is a potent histone deacetylase inhibitor with antitumor activity in both solid tumor and acute myeloid leukemia (AML) cell lines. Pracinostat has modest clinical activity in advanced solid tumors. Given the higher preclinical sensitivity of hematologic malignancies to pracinostat, we conducted a phase 1 study to assess the safety, maximum tolerated dose (MTD), recommended phase II dose (RP2D), efficacy, pharmacokinetics and pharmacodynamics of pracinostat in advanced hematological malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Injectable azacitidine 75 mg/m 2 /day, administered intravenously (IV) or subcutaneously (SC) for 7 days per 28-day treatment cycle, is approved in several countries for treatment of myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) [1,2]. Azacitidine has also been investigated in a variety of other hematologic malignancies and solid tumors [3][4][5][6]. In addition to direct cytotoxicity of proliferating malignant cells, azacitidine is incorporated into both RNA and DNA (in human AML KG1a cells, the RNA:DNA incorporation ratio was 65:35 [7]) and reduces hypermethylation in promoter regions of DNA, leading to re-expression of tumor suppressor genes and promoting differentiation of hematopoietic progenitor cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Injectable azacitidine 75 mg/m 2 /day, administered intravenously (IV) or subcutaneously (SC) for 7 days per 28-day treatment cycle, is approved in several countries for treatment of myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) [1,2]. Azacitidine has also been investigated in a variety of other hematologic malignancies and solid tumors [3][4][5][6]. In addition to direct cytotoxicity of proliferating malignant cells, azacitidine is incorporated into both RNA and DNA (in human AML KG1a cells, the RNA:DNA incorporation ratio was 65:35 [7]) and reduces hypermethylation in promoter regions of DNA, leading to re-expression of tumor suppressor genes and promoting differentiation of hematopoietic progenitor cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and pilot clinical experiences suggested the potential benefit of adding HDAC inhibitors to HMA as combination epigenetic therapy in myeloid malignancies. Data from a prior study that evaluated an HMA/pracinostat combination in subjects with MDS demonstrated preliminary clinical activity (Abaza et al , ). Based on these findings, we designed the current study to assess the safety and efficacy of the addition of pracinostat in MDS patients failing treatment with single agent HMA.…”
Section: Discussionmentioning
confidence: 99%
“…Vorinostat, panobinostat and pracinostat are oral, pan‐HDAC inhibitors. Each of these demonstrated early promise when used in combination with HMAs in single arm phase I trials (Dokmanovic et al , ; Prebet & Vey, ; Abaza et al , ). However, more recent multi‐arm randomized controlled trials have shown mixed or, in some cases, negative outcomes when combination therapy was compared with HMA monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydroxamic acid‐based compounds are among those HDAC inhibitors, which received the widely studies (Mottamal, Zheng, Huang, & Wang, ). Among them, Pracinostat 1 is a promising compound, which has been granted breakthrough therapy designation by FDA for the treatment of patients with newly diagnosed acute myelocytic leukemia (AML) who are ≥75 years of age or unfit for intensive chemotherapy(Abaza et al., ; Garcia‐Manero et al., ). Currently, Pracinostat is undergoing phase III clinical trials (Abaza et al., ; Ganai, ; Garcia‐Manero et al., ; Kang et al., ; Novotny‐Diermayr et al., ).…”
Section: Introductionmentioning
confidence: 99%